Positive electrode active material, preparation method thereof, positive electrode plate, secondary battery and electric device
Patent Information
- Application Number
- CN202380044727.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-31
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2043-03-31
AI Technical Summary
Existing secondary batteries have poor cycle performance and rate performance, especially in high-nickel systems, where cation mixing is serious, leading to a decline in electrochemical performance.
A hollow structure cathode active material with the chemical formula LiaNixCoyM1-x-yO2 is used. Nickel cobalt hydroxide is coated on the surface of the hard template agent through a co-precipitation reaction to form a tight core-shell structure. The hard template agent is subsequently calcined to remove the hard template agent to obtain a 0.3 μm -5μm hollow structure cathode active material improves the insertion and extraction efficiency of lithium ions and buffers volume changes.
It significantly improves the cycle performance and rate performance of the battery, enhances the gram capacity and energy density of the material, reduces the internal resistance of the battery, and improves the electrochemical performance.
Smart Images

Figure CN119452483A_ABST
Abstract
Description
Positive electrode active material, preparation method thereof, positive electrode sheet, secondary battery and electrical device Technical Field
[0001] The present application relates to the technical field of secondary batteries, and in particular to a positive electrode active material, a preparation method thereof, a positive electrode sheet, a secondary battery, and an electrical device. Background Art
[0002] Secondary batteries have the characteristics of high capacity and long life, so they are widely used in electronic devices such as mobile phones, laptops, electric vehicles, electric airplanes, electric ships, electric toy cars, electric toy ships, electric toy airplanes and power tools, etc. Due to the great progress made in secondary batteries, higher requirements are placed on the performance of secondary batteries. In order to improve the performance of secondary batteries, materials such as positive electrode active materials in secondary batteries are usually optimized and improved. Positive electrode active materials act as carriers of metal ions and electrons in secondary batteries, play the role of energy storage and release, and have a non-negligible impact on the performance of secondary batteries. However, when the improved positive electrode active materials are applied to secondary batteries, the cycle performance and rate performance of the secondary batteries are still poor.
[0003] Summary of the Invention
[0004] The present application is made in view of the above-mentioned problems, and its purpose is to provide a positive electrode active material having a hollow structure with an inner diameter of 0.3μm-5μm, which can effectively improve the cycle performance of the battery and at the same time the battery has excellent rate performance.
[0005] The first aspect of the present application provides a positive electrode active material, the chemical formula of the positive electrode active material is Li a Ni x Co y M 1-x-y O2,
[0006] Among them, M includes one or more of Mn, Al, B, Zr, Sr, Y, Sb, W, Ti, Mg, and Nb, 0.55≤x≤1.0, 0≤y≤0.45, and 0.8≤a≤1.2, and the positive electrode active material has a hollow structure, and the inner diameter d1 of the hollow structure is 0.3μm-5μm.
[0007] On the one hand, the hollow structure can buffer the volume changes of the positive electrode active material during the charge and discharge process, stabilizing the structure and improving cycle performance. On the other hand, the positive electrode active material with a hollow structure has more three-dimensional channels, which expands the contact area between the material and the electrolyte, shortens the migration distance of lithium ions, reduces the internal resistance of the battery, and has excellent rate performance. At the same time, the positive electrode active material with a hollow structure has more active sites for lithium ions, increasing the material's specific capacity, and improving the material's discharge capacity and energy density.
[0008] In any embodiment, the chemical formula Li a Ni x Co y M 1-x-y In O2, 0.9≤x≤1.0, 0≤y≤0.1, 0.8≤a≤1.2, optionally 0.95≤x≤0.995, 0≤y≤0.05, 0.8≤a≤1.2.
[0009] In any embodiment, the inner diameter d1 of the hollow structure is 1.5 μm-5 μm, which can further shorten the migration distance of lithium ions and improve the rate performance of the battery.
[0010] In any embodiment, the positive electrode active material satisfies the following relationship: 1≤Dv50 / (d1+d2)≤4,
[0011] Where d1μm is the inner diameter of the hollow structure, d2μm is the outer wall thickness of the hollow structure, and Dv50μm is the Dv50 of the positive electrode active material.
[0012] By controlling the Dv50 of the positive electrode active material and the inner diameter d1 and outer wall thickness d2 of the hollow structure to satisfy: 1≤Dv50 / (d1+d2)≤4, the energy density of the battery can be increased and the rate performance of the battery can be improved.
[0013] In any embodiment, the thickness d2 of the outer wall of the hollow structure is 3 μm-10 μm, and optionally 3 μm-7 μm.
[0014] By controlling the outer wall thickness d2 of the hollow structure within an appropriate range, the structural stability of the material can be improved, the battery has a high discharge capacity and energy density, excellent rate performance and cycle performance, and comprehensively improves the electrochemical performance of the battery.
[0015] In any embodiment, the Dv50 of the positive electrode active material is 5 μm-15 μm, optionally 8 μm-10 μm.
[0016] Controlling the Dv50 of the positive electrode active material within an appropriate range can improve the energy density and rate performance of the battery.
[0017] In any embodiment, the porosity of the positive electrode active material is 0-20%, optionally 2%-15%.
[0018] By controlling the porosity of the positive electrode active material within a suitable range, the battery has high discharge capacity and energy density, excellent rate performance and cycle performance, and comprehensively improves the electrochemical performance of the battery.
[0019] In any embodiment, the specific surface area of the positive electrode active material is 0.4 m 2 / g-1.4m 2 / g.
[0020] By controlling the specific surface area of the positive electrode active material within a suitable range, the battery has high discharge capacity and energy density, excellent rate performance and cycle performance, and comprehensively improves the electrochemical performance of the battery.
[0021] In any embodiment, the positive electrode active material has a SPAN of 1-1.5, optionally 1.2-1.4.
[0022] Controlling the SPAN of the positive electrode active material within an appropriate range can increase the discharge capacity of the battery.
[0023] In any embodiment, the (010) crystal plane area of the positive electrode active material is greater than or equal to 6 μm 2 .
[0024] Control the (010) crystal plane area of the positive electrode active material to be greater than or equal to 6 μm 2 The battery has high discharge capacity and energy density, excellent rate performance and cycle performance, and comprehensively improves the electrochemical performance of the battery.
[0025] In any embodiment, the primary particle size of the positive electrode active material is 0.1-0.8 μm, and optionally 0.15-0.3 μm.
[0026] Controlling the primary particle size of the positive electrode active material within an appropriate range can increase the discharge capacity and energy density of the battery and improve the battery's rate performance.
[0027] The second aspect of the present application provides a method for preparing a positive electrode active material, comprising steps (1) and (2):
[0028] Step (1): Mixing a mixed source comprising a nickel source and a cobalt source with a hard template, a complexing agent, and a precipitant to perform a coprecipitation reaction to obtain a precursor. Optionally, the mixed source contains an M source.
[0029] Step (2): calcining the precursor and lithium source to obtain the positive electrode active material,
[0030] The chemical formula of the positive electrode active material is Lia Ni x Co y M 1-x-y O2,
[0031] Wherein, M includes one or more of Mn, Al, B, Zr, Sr, Y, Sb, W, Ti, Mg, and Nb, 0.55≤x≤1.0, 0≤y≤0.45, and 0.8≤a≤1.2. The positive electrode active material has a hollow structure, and the inner diameter of the hollow structure is 0.3 μm to 5 μm.
[0032] A coprecipitation reaction is used to coat a dense layer of nickel-cobalt hydroxide on the surface of a hard template, forming a compact core-shell structure. The hard template is subsequently removed by calcination to obtain a positive electrode active material with a hollow structure. The preparation method of the above-mentioned positive electrode active material is simple and has low production cost. The prepared positive electrode active material has a hollow structure with an inner diameter of 0.3μm to 5μm, which is conducive to the insertion and extraction of lithium ions. At the same time, the hollow structure can buffer the volume change of the positive electrode active material during the charge and discharge process, stabilizing the structure and improving the cycle performance.
[0033] In any embodiment, the chemical formula Li a Ni x Co y M 1-x-y In O2, 0.9≤x≤1.0, 0≤y≤0.1, 0.8≤a≤1.2, optionally 0.95≤x≤0.995, 0≤y≤0.05, 0.8≤a≤1.2.
[0034] In any embodiment, the average diameter of the hard template is 0.2 μm to 3 μm, optionally 1 μm to 3 μm.
[0035] Controlling the average diameter of the hard template within a suitable range, and then controlling the inner diameter of the hollow structure of the positive electrode active material within a suitable range, can take into account both the diffusion path of lithium ions and the stability of the hollow structure, and comprehensively improve the cycle performance and rate performance of the battery.
[0036] In any embodiment, the hard template includes one or more of carbon-nitrogen composite balls, carbon balls, phenolic resin microballoons, and melamine resin microballoons, and optionally includes phenolic resin balls.
[0037] In any embodiment, the ratio of the weight of the hard template added in step (1) to the total weight of the nickel element and the cobalt element in the mixed source is 1:20-3:4,
[0038] Alternatively, the ratio of the weight of the hard template added in step (1) to the total weight of the nickel element, the cobalt element and the M element in the mixed source is 1:20-3:4.
[0039] The total weight of the hard template and the nickel element, cobalt element and / or M element in the mixed source is controlled within an appropriate range, so that the nickel cobalt hydroxide layer is stably and uniformly coated on the surface of the hard template, so that the hollow structure has a suitable inner diameter and outer wall thickness, the positive electrode active material has excellent structural properties, and the cycle performance and rate performance of the battery are improved.
[0040] In any embodiment, the pH value of the coprecipitation reaction in step (1) is 9-13.
[0041] The appropriate pH value of the co-precipitation reaction makes the co-precipitation reaction smoother and more efficient, so that the nickel cobalt hydroxide layer is stably and evenly coated on the surface of the hard template, so that the hollow structure has a suitable inner diameter and outer wall thickness, and the positive electrode active material has excellent structural properties, thereby improving the cycle performance and rate performance of the battery.
[0042] In any embodiment, the reaction temperature of the co-precipitation reaction in step (1) is 60-85°C.
[0043] The appropriate co-precipitation reaction temperature makes the co-precipitation reaction smoother and more efficient, so that the nickel cobalt hydroxide layer is stably and evenly coated on the surface of the hard template, so that the hollow structure has a suitable inner diameter and outer wall thickness, and the positive electrode active material has excellent structural properties, thereby improving the cycle performance and rate performance of the battery.
[0044] In any embodiment, the reaction time of the co-precipitation reaction in step (1) is 5-20 hours.
[0045] The appropriate reaction time of the co-precipitation reaction makes the co-precipitation reaction smoother and more efficient, so that the nickel-cobalt hydroxide layer is stably and evenly coated on the surface of the hard template, so that the hollow structure has a suitable inner diameter and outer wall thickness, and the positive electrode active material has excellent structural properties, thereby improving the cycle performance and rate performance of the battery.
[0046] In any embodiment, the stirring speed of the co-precipitation reaction in step (1) is 200-900 rpm.
[0047] The appropriate co-precipitation reaction stirring speed makes the co-precipitation reaction smoother and more efficient, so that the nickel cobalt hydroxide layer is stably and evenly coated on the surface of the hard template, so that the hollow structure has a suitable inner diameter and outer wall thickness, and the positive electrode active material has excellent structural properties, thereby improving the cycle performance and rate performance of the battery.
[0048] In any embodiment, step (1) specifically includes:
[0049] Prepare a hard template solution with a mass concentration of 1-10 g / L, a precipitant solution with a molar concentration of 1-2 mol / L, a complexing agent solution with a molar concentration of 4-8 mol / L, and a mixed salt solution containing nickel and cobalt with a total molar concentration of 1-2 mol / L, and optionally the mixed salt solution further contains element M;
[0050] adding the precipitant solution, the complexing agent solution and the mixed salt solution together into the hard template solution;
[0051] A coprecipitation reaction is carried out to obtain a precursor.
[0052] By controlling the hard template, precipitant, complexing agent, and mixed salt solution within an appropriate range, the coprecipitation reaction is smoother and more efficient. During the coprecipitation reaction, nickel cobalt hydroxide can be precipitated more slowly, stably, and densely on the surface of the hard template, forming a more uniform shell structure on the surface of the hard template, so that the hollow structure has a suitable inner diameter, outer wall thickness, and Dv50, and the positive electrode active material has excellent structural properties, thereby improving the cycle performance and rate performance of the battery.
[0053] In any embodiment, the calcination temperature in step (2) is 700-900°C;
[0054] The calcination time in step (2) is 6-18h.
[0055] The calcination temperature and time are controlled within an appropriate range to ensure that the hard template can be completely removed to form a hollow structure. At the same time, the stability of the positive electrode active material structure must be ensured. The positive electrode active material has a stable hollow structure to improve the cycle performance and rate performance of the battery.
[0056] A third aspect of the present application provides a positive electrode plate, which includes the positive electrode active material of the first aspect or the positive electrode active material prepared by the preparation method of the second aspect.
[0057] A fourth aspect of the present application provides a secondary battery comprising the positive electrode sheet of the third aspect.
[0058] A fifth aspect of the present application provides an electrical device comprising the secondary battery of the fourth aspect. BRIEF DESCRIPTION OF THE DRAWINGS
[0059] FIG1 is a scanning electron microscope image of the positive electrode active material shown in Example 4 of the present application;
[0060] FIG2 is a schematic diagram of a secondary battery according to an embodiment of the present application;
[0061] FIG3 is an exploded view of the secondary battery according to one embodiment of the present application shown in FIG2 ;
[0062] FIG4 is a schematic diagram of a battery module according to an embodiment of the present application;
[0063] FIG5 is a schematic diagram of a battery pack according to an embodiment of the present application;
[0064] FIG6 is an exploded view of the battery pack shown in FIG5 according to an embodiment of the present application;
[0065] 7 is a schematic diagram of an electrical device using a secondary battery as a power source according to an embodiment of the present application;
[0066] Explanation of reference numerals: 1 battery pack; 2 upper case; 3 lower case; 4 battery module; 5 secondary battery; 51 housing; 52 electrode assembly; 53 cover plate. DETAILED DESCRIPTION
[0067] Below, the embodiments of the positive electrode active material, preparation method thereof, secondary battery and electric device of the present application are described in detail with appropriate reference to the drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0068] " range " disclosed in the present application is limited in the form of lower limit and upper limit, and given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of special range. The scope limited in this way can be to include end value or not include end value, and can be arbitrarily combined, that is, any lower limit can form a range with any upper limit combination. For example, if the scope of 60-120 and 80-110 is listed for specific parameters, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range value 1 and 2 are listed, and if the maximum range value 3,4 and 5 are listed, then the following range can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In this application, unless otherwise specified, the numerical range " ab " represents the abbreviation of any real number combination between a and b, wherein a and b are all real numbers. For example, a numerical range of "0-5" indicates that all real numbers between "0-5" are listed herein, and "0-5" is simply an abbreviation for these numerical combinations. Furthermore, when a parameter is expressed as an integer ≥ 2, this is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0069] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0070] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0071] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), indicating that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0072] Unless otherwise specified, the terms "include" and "comprising" used in this application may be open-ended or closed-ended. For example, "include" and "comprising" may mean that other components not listed may also be included or that only the listed components are included.
[0073] Unless otherwise specified, the term "or" is used in this application to be inclusive. For example, the phrase "A or B" means "A, B, or both A and B." More specifically, the condition "A or B" is satisfied if any of the following conditions are met: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0074] In the existing technology, nickel-rich ternary materials have become one of the popular secondary battery positive electrode active materials due to their high theoretical specific capacity, high discharge platform and low cost. +2 Ionic radius and Li + When the radii are close, the phenomenon of cation mixing will seriously occur, causing the electrochemical performance of the material to decline. Especially in high-nickel systems, the cation mixing trend increases and the battery cycle performance deteriorates. On the other hand, during the charge and discharge process of lithium-ion batteries, due to the existence of interfacial side reactions, the electrolyte will continue to decompose at the interface of the positive and negative electrodes, and the positive electrode active material will undergo an interfacial phase change, resulting in the loss of active Li and an increase in the impedance of the lithium-ion battery, resulting in a decrease in the rate performance of the material. It is necessary to develop a positive electrode active material with high specific capacity, excellent cycle performance and rate performance to meet the application needs of the new generation of electrochemical systems.
[0075] [Positive electrode active material]
[0076] Based on this, the present application proposes a positive electrode active material, the chemical formula of which is Li a Nix Co y M 1-x-y O2,
[0077] Among them, M includes one or more of Mn, Al, B, Zr, Sr, Y, Sb, W, Ti, Mg, and Nb, 0.55≤x≤1.0, 0≤y≤0.45, and 0.8≤a≤1.2, and the positive electrode active material has a hollow structure, and the inner diameter d1 of the hollow structure is 0.3μm-5μm.
[0078] As used herein, the term "hollow structure" refers to a solid structure with an internal cavity surrounded by a distinct shell.
[0079] Herein, the term "inner diameter of the hollow structure" refers to the longest diameter of a circular or quasi-circular cross-section of the internal cavity of the positive electrode active material.
[0080] The inner diameter of the hollow structure can be tested by any means known in the art. As an example, a conductive glue is attached to the sample table, a powdered sample of the positive electrode active material is spread on the conductive glue, the unadhered powder is blown away with an ear bulb, gold is sprayed, and the particles of the powdered sample are cross-sectioned using argon plasma. A scanning electron microscope is used to obtain a scanning electron microscope photo of the powdered sample at an acceleration voltage of 10kV and an emission current of 10mA. According to the scanning electron microscope photo, the inner diameter of the hollow structure is measured, at least three samples are measured, at least 50 data are measured for each sample, and the number average value is taken as the inner diameter of the hollow structure of the sample.
[0081] In some embodiments, the chemical formula Li a Ni x Co y M 1-x-y In O2, a is any value among 0.8, 0.9, 1.0, 1.1, 1.2, or a range consisting of any two values thereof.
[0082] In some embodiments, the chemical formula Li a Ni x Co y M 1-x-y In O2, x is any value selected from 0.55, 0.6, 0.7, 0.8, 0.9, 0.95, and 0.995, or a range consisting of any two of these values.
[0083] In some embodiments, the chemical formula Li a Ni x Co y M 1-x-y In O2, y is any value among 0, 0.1, 0.2, 0.3, 0.4, 0.45, or a range consisting of any two values thereof.
[0084] In some embodiments, the chemical formula Li a Ni x Co y M 1-x-y In O2, 0.90≤x≤1.0, 0≤y≤0.1, 0.8≤a≤1.2.
[0085] In some embodiments, the chemical formula Li a Ni x Co y M 1-x-y In O2, 0.95≤x≤0.995, 0≤y≤0.05, 0.8≤a≤1.2.
[0086] In some embodiments, the positive electrode active material has the chemical formula Li a Ni x Co y Mn 1-x- y O2, 0.95≤x≤0.995, 0≤y≤0.05, 0.8≤a≤1.2.
[0087] In some embodiments, the positive electrode active material has the chemical formula Li a Ni x Co y Sb 1-x-y O2, 0.95≤x≤0.995, 0≤y≤0.05, 0.8≤a≤1.2.
[0088] In some embodiments, the positive electrode active material has the chemical formula Li a Ni x Co y O2, 0.95≤x≤0.995, 0.005≤y≤0.05, x+y=1, 0.8≤a≤1.2.
[0089] The use of the above materials can ensure that the positive electrode active material has a high gram capacity, so that the battery has a high discharge capacity and energy density.
[0090] In some embodiments, the inner diameter d1 of the hollow structure can be selected as any one of 0.3μm-0.5μm, 0.3μm-0.9μm, 0.3μm-1μm, 0.3μm-2μm, 0.3μm-3μm, 0.3μm-4μm, 0.3μm-5μm, 1μm-2μm, 1μm-3μm, 1μm-4μm, 1μm-5μm, 2μm-3μm, 2μm-4μm, 2μm-5μm, 3μm-4μm, 3μm-5μm, and 4μm-5μm.
[0091] On the one hand, the hollow structure can buffer the volume changes of the positive electrode active material during the charge and discharge process, stabilizing the structure and improving cycle performance. On the other hand, the positive electrode active material with a hollow structure has more three-dimensional channels, which expands the contact area between the material and the electrolyte, shortens the migration distance of lithium ions, reduces the internal resistance of the battery, and has excellent rate performance. At the same time, the positive electrode active material with a hollow structure has more active sites for lithium ions, increasing the material's specific capacity, and improving the material's discharge capacity and energy density.
[0092] In some embodiments, the inner diameter d1 of the hollow structure is 1.5 μm-5 μm. In some embodiments, the inner diameter d1 of the hollow structure can be any one of 1.5 μm-3 μm, 2 μm-4 μm, 2 μm-5 μm, 3 μm-4 μm, 3 μm-5 μm, and 4 μm-5 μm.
[0093] When the inner diameter d1 of the hollow structure is within a suitable range, the migration distance of lithium ions can be further shortened and the rate performance of the battery can be improved.
[0094] In some embodiments, the positive electrode active material satisfies the following relationship: 1≤Dv50 / (d1+d2)≤4,
[0095] Where d1μm is the inner diameter of the hollow structure, d2μm is the outer wall thickness of the hollow structure, and Dv50μm is the Dv50 of the positive electrode active material.
[0096] In some embodiments, the positive electrode active material satisfies any one of the following relationships: 1≤Dv50 / (d1+d2)≤2, 1≤Dv50 / (d1+d2)≤3, 1≤Dv50 / (d1+d2)≤4, 2≤Dv50 / (d1+d2)≤3, 2≤Dv50 / (d1+d2)≤4, 3≤Dv50 / (d1+d2)≤4,
[0097] Where d1μm is the inner diameter of the hollow structure, d2μm is the outer wall thickness of the hollow structure, and Dv50μm is the Dv50 of the positive electrode active material.
[0098] Herein, the term "outer wall thickness of the hollow structure" refers to the thickness of the outer shell of the hollow structure.
[0099] The thickness of the outer wall of the hollow structure can be tested by any means known in the art. As an example, a conductive glue is attached to the sample table, a powdered sample of the positive electrode active material is spread on the conductive glue, the unadhered powder is blown away with an ear bulb, gold is sprayed, and the particles of the powdered sample are cross-sectioned using argon plasma. A scanning electron microscope is used to obtain a scanning electron microscope photo of the powdered sample at an accelerating voltage of 10kV and an emission current of 10mA. The outer wall thickness of the hollow structure is measured according to the scanning electron microscope image, at least three samples are measured, at least 50 data are measured for each sample, and the number average value is taken as the outer wall thickness of the hollow structure of the sample.
[0100] As used herein, the term "Dv50" refers to the median particle size of the positive electrode active material. Specifically, Dv50 represents the particle size at which the cumulative volume of the positive electrode active material reaches 50% from the smallest particle size in the volume-based particle size distribution.
[0101] The Dv50 of the positive electrode active material can be measured by any means known in the art. As an example, the Dv50 value of the positive electrode active material can be measured according to the method specified in GB / T19077-2016.
[0102] The positive electrode active material's Dv50, the inner diameter d1 of the hollow structure, and the outer wall thickness d2 are important parameters of the positive electrode active material structure, influencing the material's structural performance. When these values are within the appropriate range, the material possesses more active sites for lithium ions, increasing its specific capacity and, consequently, its battery density. This also improves the material's structural stability, effectively mitigates the lithium-nickel intermixing phenomenon, and significantly increases the migration rate of lithium ions and electrons, thus enhancing the material's rate performance.
[0103] By controlling the Dv50 of the positive electrode active material and the inner diameter d1 and outer wall thickness d2 of the hollow structure to satisfy: 1≤Dv50 / (d1+d2)≤4, the energy density of the battery can be increased and the rate performance of the battery can be improved.
[0104] In some embodiments, the outer wall thickness d2 of the hollow structure is 3 μm-10 μm. In some embodiments, the outer wall thickness d2 of the hollow structure can be selected from 3 μm-4 μm, 3 μm-5 μm, 3 μm-6 μm, 3 μm-7 μm, 3 μm-8 μm, 3 μm-9 μm, 3 μm-10 μm, 4 μm-5 μm, 4 μm-6 μm, 4 μm-7 μm, 4 μm-8 μm, 4 μm-9 μm, 4 μm-10 μm, 5 μm-6 μm, 5 ... μm-6μm, 5μm-7μm, 5μm-8μm, 5μm-9μm, 5μm-10μm, 6μm-7μm, 6μm-8μm, 6μm-9μm, 6 Any one of μm-10μm, 7μm-8μm, 7μm-9μm, 7μm-10μm, 8μm-9μm, 8μm-10μm, and 9μm-10μm.
[0105] By controlling the outer wall thickness d2 of the hollow structure within an appropriate range, the structural stability of the material can be improved, the battery has a high discharge capacity and energy density, excellent rate performance and cycle performance, and comprehensively improves the electrochemical performance of the battery.
[0106] In some embodiments, the outer wall thickness d2 of the hollow structure is 3 μm-7 μm. In some embodiments, the outer wall thickness d2 of the hollow structure can be selected from any one of 3 μm-4 μm, 3 μm-5 μm, 3 μm-6 μm, 3 μm-7 μm, 4 μm-5 μm, 4 μm-6 μm, 4 μm-7 μm, 5 μm-6 μm, 5 μm-7 μm, and 6 μm-7 μm.
[0107] When the outer wall thickness of the hollow structure is within an appropriate range, the cycle performance and rate performance of the battery can be further improved.
[0108] In some embodiments, the Dv50 of the positive electrode active material is 5 μm-15 μm. In some embodiments, the Dv50 of the positive electrode active material is any one of 5 μm-9 μm, 5 μm-10 μm, 5 μm-15 μm, 9 μm-10 μm, 9 μm-15 μm, and 10 μm-15 μm.
[0109] Particles of different sizes have different areas and different numbers of reactive sites. Therefore, the size of the particles will affect the speed of ion embedding and deintercalation, and the gram capacity of the material. Controlling the Dv50 of the positive electrode active material within an appropriate range can improve the energy density and rate performance of the battery.
[0110] In some embodiments, the Dv50 of the positive electrode active material is 8 μm-10 μm. In some embodiments, the Dv50 of the positive electrode active material is any one of 8 μm-9 μm, 8 μm-10 μm, and 9 μm-10 μm.
[0111] Controlling the Dv50 of the positive electrode active material within an appropriate range can further improve the energy density and rate performance of the battery.
[0112] In some embodiments, the porosity of the positive electrode active material is 0-20%. In some embodiments, the porosity of the positive electrode active material can be selected from any one of 0-5%, 0-10%, 0-15%, 0-20%, 5-10%, 5-15%, 5-20%, 10-15%, 10-20%, and 15-20%.
[0113] Herein, “porosity” refers to the ratio of the volume of pores in the positive electrode active material to the total volume of the positive electrode active material.
[0114] The porosity of the positive electrode active material can be measured using any method known in the art. For example, the porosity is measured using the gas displacement method according to GB / T 24586. Porosity = (V1 - V2) / V1 * 100%, where V1 is the apparent volume of the sample and V2 is the actual volume of the sample.
[0115] Controlling the porosity of the positive electrode active material within an appropriate range is beneficial to the infiltration of the electrolyte, allowing the positive electrode active material to fully contact the electrolyte, shortening the lithium ion transmission path, and the battery having high discharge capacity and energy density, excellent rate performance and cycle performance, and comprehensively improving the electrochemical performance of the battery.
[0116] In some embodiments, the porosity of the positive electrode active material is 2-15%. In some embodiments, the porosity of the positive electrode active material can be any one of 2-5%, 2-10%, 2-15%, 5-10%, 5-15%, and 10-15%.
[0117] Controlling the porosity of the positive electrode active material within an appropriate range can further increase the discharge capacity and energy density of the battery, and improve the battery's rate performance and cycle performance.
[0118] In some embodiments, the specific surface area of the positive electrode active material is 0.4 m 2 / g-1.4m 2 In some embodiments, the specific surface area of the positive electrode active material may be 0.4 m 2 / g-0.7m 2 / g, 0.4m 2 / g-0.9m 2 / g, 0.5m 2 / g-0.7m 2 / g, 0.5m 2 / g-0.9m 2 / g, 0.5m 2 / g-1.1m2 / g, 0.7m 2 / g-0.9m 2 / g, 0.7m 2 / g-1.1m 2 / g, 0.9m 2 / g-1.1m 2 Any of / g.
[0119] The specific surface area of the positive electrode active material can be measured using any method known in the art. For example, reference can be made to GB / T 19587-2017, "Determination of the Specific Surface Area of Solid Materials by the BET Method for Gas Adsorption." The measurement is performed using a TriStar II 3020 instrument. The positive electrode active material is dispersed in a dispersant (ethanol), ultrasonicated for 30 minutes, and then dried in a vacuum drying oven. Finally, the specific surface area of the positive electrode active material is measured using a specific surface area meter.
[0120] The larger the specific surface area of the positive electrode active material, the more active sites in the positive electrode active material, the faster the exchange rate between the positive electrode active material and electrons, and the better the battery's kinetic performance. However, too many active sites will increase the side reactions between the positive electrode active material and the electrolyte, worsening the battery's cycle performance, while too few active sites will lead to a decrease in the chemical reaction in the battery system, resulting in poor battery capacity and cycle performance.
[0121] By controlling the specific surface area of the positive electrode active material within a suitable range, the battery has high discharge capacity and energy density, excellent rate performance and cycle performance, and comprehensively improves the electrochemical performance of the battery.
[0122] In some embodiments, the SPAN of the positive electrode active material is 1-1.5. In some embodiments, the SPAN of the positive electrode active material can be selected from any one of 1-1.1, 1-1.2, 1-1.3, 1-1.4, 1-1.5, 1.1-1.2, 1.1-1.3, 1.1-1.4, 1.1-1.5, 1.2-1.3, 1.2-1.4, 1.2-1.5, 1.3-1.4, 1.3-1.5, and 1.4-1.5.
[0123] In this article, the term "SPAN" refers to the distribution span. SPAN is calculated as (Dv90-Dv10) / Dv50, which represents the particle distribution of the positive electrode active material, where Dv50 represents the particle size of the positive electrode active material in the volume-based particle size distribution, starting from the small particle size side and reaching 50% of the volume accumulation; Dv10 represents the particle size of the positive electrode active material in the volume-based particle size distribution, starting from the small particle size side and reaching 10% of the volume accumulation; Dv90 represents the particle size of the positive electrode active material in the volume-based particle size distribution, starting from the small particle size side and reaching 90% of the volume accumulation.
[0124] The Dv50, Dv10, and Dv90 values of the positive electrode active material were measured according to the method specified in GB / T19077-2016, and the SPAN of the positive electrode active material was then calculated.
[0125] Maintaining SPAN in a wider range can increase the compaction density of the material and improve the discharge capacity of the battery.
[0126] In some embodiments, the SPAN of the positive electrode active material is 1.2-1.4. In some embodiments, the SPAN of the positive electrode active material can be selected from any one of 1.2-1.3, 1.2-1.4, and 1.3-1.4.
[0127] SPAN is maintained in a wide range, with particles of different sizes, which avoids the cracking of particles during battery cycling and makes the battery have excellent cycle performance; the synthesized precursor particles are uneven in size, and the particles are in close contact with each other, which improves the transmission speed of lithium ions and makes the battery have excellent rate performance.
[0128] By controlling the SPAN of the positive electrode active material within an appropriate range, the cycle performance and rate performance of the battery can be taken into account, and the electrochemical performance of the battery can be comprehensively improved.
[0129] In some embodiments, the (010) crystal plane area of the positive electrode active material is greater than or equal to 6 μm 2 .
[0130] In some embodiments, the (010) crystal plane area of the positive electrode active material is greater than or equal to 6 μm 2 , 20μm 2 , 50μm 2 , 100μm 2 , 150μm 2 , 200μm 2 , 240μm 2 , 250μm 2 Any one of .
[0131] The (010) crystal plane area of the positive electrode active material can be measured by any means known in the art. As an example, the (101) crystal plane area is measured using an X-ray powder diffractometer (XRD, instrument model: Bruker D8 ADVANCE), with a Cu Kα target; the voltage and current are 40 kV / 40 mA, the scanning angle range is 5° to 80°, the scanning step length is 0.00836°, and the time per step is 0.3 s.
[0132] The (010) crystal plane is the dominant plane for lithium ion transmission. The positive electrode active material has a large (010) crystal plane area, the positive electrode active material has a large number of lithium ion reaction active sites, and the battery has excellent kinetic performance.
[0133] Control the (010) crystal plane area of the positive electrode active material to be greater than or equal to 6 μm 2 The battery has high discharge capacity and energy density, excellent rate performance and cycle performance, and comprehensively improves the electrochemical performance of the battery.
[0134] In some embodiments, the primary particle size of the positive electrode active material is 0.1-0.8 μm. In some embodiments, the primary particle size of the positive electrode active material can be selected from 0.1-0.2 μm, 0.1-0.3 μm, 0.1-0.4 μm, 0.1-0.5 μm, 0.1-0.6 μm, 0.1-0.7 μm, 0.1-0.8 μm, 0.2-0.3 μm, 0.2-0.4 μm, 0.2-0.5 μm, 0.2-0.6 μm, 0.2-0.7 μm, 0.2-0.8 μm, Any one of 0.3-0.4μm, 0.3-0.5μm, 0.3-0.6μm, 0.3-0.7μm, 0.3-0.8μm, 0.4-0.5μm, 0.4-0.6μm, 0.4-0.7μm, 0.4-0.8μm, 0.5-0.6μm, 0.5-0.7μm, 0.5-0.8μm, 0.6-0.7μm, 0.6-0.8μm, 0.7-0.8μm.
[0135] Herein, the term "primary particles" refers to particles of the positive electrode active material before agglomeration.
[0136] The particle size of the primary particles of the positive electrode active material can be measured using any method known in the art. As an example, after imaging using a scanning electron microscope at 500x magnification, 200 to 600 intact, unobstructed primary particles of the positive electrode active material are randomly selected from the electron microscopic image. The average of the longest diameters of the primary particles in the microscopic image is recorded as the average particle size.
[0137] By controlling the primary particle size of the positive electrode active material within an appropriate range, shortening the lithium ion diffusion path, and accelerating the rate of lithium ion insertion and extraction, the discharge capacity and energy density of the battery can be increased, and the battery's rate performance can be improved.
[0138] In some embodiments, the primary particle size of the positive electrode active material is 0.15-0.3 μm. In some embodiments, the primary particle size of the positive electrode active material can be any one of 0.15-0.2 μm, 0.15-0.3 μm, and 0.2-0.3 μm.
[0139] By controlling the particle size of the primary particles of the positive electrode active material within a suitable range, the primary particles have excellent structural stability. During the cyclic charge and discharge process, as lithium ions repeatedly escape from and embed into the primary particles, the primary particles can still maintain their complete structure, reducing the phenomenon of transition metals inside the primary particles escaping from the primary particles and dissolving into the electrolyte, thereby improving the cycle stability of the battery.
[0140] In some embodiments, the gram capacity of the positive electrode active material is 238 mAh / g to 250 mAh / g.
[0141] The specific capacity of the positive electrode active material can be measured using any method known in the art. For example, at 25°C and atmospheric pressure, a button cell is charged at a constant current rate of 0.02C to a voltage of 3.5V. This is followed by a constant current charge of 0.1C to a voltage of 4.3V, followed by a constant voltage charge of 4.3V until the current drops to 0.05C. The charge specific capacity at this point is recorded as the initial lithium removal capacity. The cell is then discharged at a constant current rate of 0.1C to a voltage of 2.5V, and the discharge specific capacity at this point is recorded as the initial lithium insertion capacity. The specific capacity of the positive electrode active material in grams is the initial lithium insertion capacity.
[0142] The present application also proposes a method for preparing a positive electrode active material, comprising steps (1) and (2):
[0143] Step (1): Mixing a mixed source comprising a nickel source and a cobalt source with a hard template, a complexing agent, and a precipitant to perform a coprecipitation reaction to obtain a precursor. Optionally, the mixed source contains an M source.
[0144] Step (2): calcining the precursor and lithium source to obtain the positive electrode active material,
[0145] The chemical formula of the positive electrode active material is Li a Ni x Co y M 1-x-y O2,
[0146] Among them, M includes one or more of Mn, Al, B, Zr, Sr, Y, Sb, W, Ti, Mg, and Nb, 0.55≤x≤1.0, 0≤y≤0.45, and 0.8≤a≤1.2. The positive electrode active material has a hollow structure, and the inner diameter of the hollow structure is 0.3μm to 5μm.
[0147] In this article, the term "co-precipitation reaction" refers to a precipitation reaction in which a metal solution, a precipitant, and a complexing agent are reacted together at a certain temperature.
[0148] In some embodiments, the M source is a manganese source or an antimony source.
[0149] In some embodiments, the method for preparing a positive electrode active material comprises steps (1) and (2):
[0150] Step (1): Mixing a mixed source containing a nickel source and a cobalt source with a hard template, a complexing agent, and a precipitant to perform a coprecipitation reaction to obtain a precursor.
[0151] Step (2): calcining the precursor and the lithium source to obtain the positive electrode active material.
[0152] In some embodiments, the nickel source includes one or more of nickel sulfate, nickel hydrochloride, nickel nitrate, and nickel acetate.
[0153] In some embodiments, the cobalt source includes one or more of cobalt sulfate, cobalt hydrochloride, cobalt nitrate, and cobalt acetate.
[0154] In some embodiments, the manganese source includes one or more of manganese sulfate, manganese hydrochloride, manganese nitrate, and manganese acetate.
[0155] In some embodiments, the antimony source includes one or more of antimony sulfate, antimony hydrochloride, antimony nitrate, and antimony acetate.
[0156] A coprecipitation reaction is used to coat a dense layer of nickel-cobalt hydroxide on the surface of a hard template, forming a compact core-shell structure. The hard template is subsequently removed by calcination to obtain a positive electrode active material with a hollow structure. The preparation method of the above-mentioned positive electrode active material is simple and has low production cost. The prepared positive electrode active material has a hollow structure with an inner diameter of 0.3μm to 5μm, which is conducive to the insertion and extraction of lithium ions. At the same time, the hollow structure can buffer the volume change of the positive electrode active material during the charge and discharge process, stabilizing the structure and improving the cycle performance.
[0157] In some embodiments, the chemical formula Li a Ni x Co y M 1-x-y In O2, 0.9≤x≤1.0, 0≤y≤0.1, 0.8≤a≤1.2.
[0158] In some embodiments, the chemical formula LiaNi x Co y M 1-x-y In O2, 0.95≤x≤0.995, 0≤y≤0.05, 0.8≤a≤1.2.
[0159] In some embodiments, the average diameter of the hard template is 0.2 μm-3 μm. In some embodiments, the average diameter of the hard template can be any one of 0.2 μm-1 μm, 0.2 μm-2 μm, 0.2 μm-3 μm, 1 μm-2 μm, 1 μm-3 μm, and 2 μm-3 μm.
[0160] In some embodiments, the average diameter of the hard template is 1 μm-3 μm. In some embodiments, the average diameter of the hard template can be any one of 1 μm-2 μm, 1 μm-3 μm, and 2 μm-3 μm.
[0161] Controlling the average diameter of the hard template within a suitable range, and then controlling the inner diameter of the hollow structure of the positive electrode active material within a suitable range, can take into account both the diffusion path of lithium ions and the stability of the hollow structure, and comprehensively improve the cycle performance and rate performance of the battery.
[0162] In some embodiments, the hard template includes one or more of carbon-nitrogen composite spheres, carbon spheres, phenolic resin microspheres, and melamine resin microspheres.
[0163] In some embodiments, the hard templating agent comprises phenolic resin spheres.
[0164] The suitable hard template has excellent adsorption properties, so that a dense layer of nickel-cobalt hydroxide can be formed on the surface of the hard template in the coprecipitation reaction. The positive electrode active material has excellent structural properties, which improves the cycle performance and rate performance of the battery.
[0165] In some embodiments, the ratio of the weight of the hard template added in step (1) to the total weight of the nickel element and the cobalt element in the mixed source is 1:20-3:4.
[0166] In some embodiments, the ratio of the weight of the hard template added in step (1) to the total weight of the nickel element, the cobalt element and the M element in the mixed source is 1:20-3:4.
[0167] In some embodiments, the ratio of the weight of the hard template added in step (1) to the total weight of the nickel element and the cobalt element in the mixed source is any value of 1:20, 1:15, 1:10, 1:5, 1:4, 2:4, 3:4, or a range consisting of any two values thereof.
[0168] In some embodiments, the ratio of the weight of the hard template added in step (1) to the total weight of the nickel element, cobalt element and M element in the mixed source is any value of 1:20, 1:15, 1:10, 1:5, 1:4, 2:4, 3:4 or a range consisting of any two values thereof.
[0169] In some embodiments, the ratio of the weight of the hard template added in step (1) to the total weight of nickel, cobalt and manganese in the mixed source is any value of 1:20, 1:15, 1:10, 1:5, 1:4, 2:4, 3:4 or a range consisting of any two of these values.
[0170] The total weight of the hard template and the nickel element, cobalt element and / or M element in the mixed source is controlled within an appropriate range, so that the nickel cobalt hydroxide layer is stably and uniformly coated on the surface of the hard template, so that the hollow structure has a suitable inner diameter and outer wall thickness, the positive electrode active material has excellent structural properties, and the cycle performance and rate performance of the battery are improved.
[0171] In some embodiments, the pH value of the coprecipitation reaction in step (1) is 9-13.
[0172] In some embodiments, the pH value is any of 9, 10, 11, 12, 13, or a range consisting of any two of these values.
[0173] The appropriate pH value of the co-precipitation reaction makes the co-precipitation reaction smoother and more efficient, so that the nickel cobalt hydroxide layer is stably and evenly coated on the surface of the hard template, so that the hollow structure has a suitable inner diameter and outer wall thickness, and the positive electrode active material has excellent structural properties, thereby improving the cycle performance and rate performance of the battery.
[0174] In some embodiments, the reaction temperature of the co-precipitation reaction in step (1) is 60-85°C.
[0175] In some embodiments, the reaction temperature is any value of 60°C, 70°C, 80°C, 85°C, or a range consisting of any two values thereof.
[0176] The appropriate co-precipitation reaction temperature makes the co-precipitation reaction smoother and more efficient, so that the nickel cobalt hydroxide layer is stably and evenly coated on the surface of the hard template, so that the hollow structure has a suitable inner diameter and outer wall thickness, and the positive electrode active material has excellent structural properties, thereby improving the cycle performance and rate performance of the battery.
[0177] In some embodiments, the reaction time of the co-precipitation reaction in step (1) is 5-20 hours.
[0178] In some embodiments, the reaction time is any value among 5 h, 10 h, 15 h, 20 h, or a range consisting of any two values therein.
[0179] The appropriate reaction time of the co-precipitation reaction makes the co-precipitation reaction smoother and more efficient, so that the nickel-cobalt hydroxide layer is stably and evenly coated on the surface of the hard template, so that the hollow structure has a suitable inner diameter and outer wall thickness, and the positive electrode active material has excellent structural properties, thereby improving the cycle performance and rate performance of the battery.
[0180] In some embodiments, the stirring speed of the co-precipitation reaction in step (1) is 200-900 rpm.
[0181] In some embodiments, the reaction stirring speed is any value of 200 rpm, 300 rpm, 400 rpm, 500 rpm, 600 rpm, 700 rpm, 800 rpm, 900 rpm, or a range consisting of any two values thereof.
[0182] The appropriate stirring speed of the co-precipitation reaction makes the co-precipitation reaction smoother and more efficient, so that the nickel-cobalt hydroxide layer is stably and evenly coated on the surface of the hard template, so that the hollow structure has a suitable inner diameter and outer wall thickness, the positive electrode active material has excellent structural properties, and the cycle performance and rate performance of the battery are improved.
[0183] In some embodiments, step (1) specifically includes:
[0184] Prepare a hard template solution with a mass concentration of 1-10 g / L, a precipitant solution with a molar concentration of 1-2 mol / L, a complexing agent solution with a molar concentration of 4-8 mol / L, and a mixed salt solution containing nickel and cobalt with a total molar concentration of 1-2 mol / L, and optionally the mixed salt solution further contains element M;
[0185] adding the precipitant solution, the complexing agent solution and the mixed salt solution together into the hard template solution;
[0186] A coprecipitation reaction is carried out to obtain a precursor.
[0187] In some embodiments, the precipitant includes one or more of sodium hydroxide, sodium carbonate, sodium bicarbonate, ammonium bicarbonate, and optionally ammonium bicarbonate.
[0188] In some embodiments, the complexing agent includes one or more of ammonia water, lactic acid, polyvinyl pyrrolidone, and can be ammonia water.
[0189] In some embodiments, the mass concentration of the hard template solution is any value of 1 g / L, 2 g / L, 3 g / L, 4 g / L, 5 g / L, 6 g / L, 7 g / L, 8 g / L, 9 g / L, 10 g / L, or a range consisting of any two values thereof.
[0190] In some embodiments, the molar concentration of the precipitant solution is any value of 1 mol / L, 1.5 mol / L, 2 mol / L, or a range consisting of any two values thereof.
[0191] In some embodiments, the molar concentration of the complexing agent solution is any value of 4 mol / L, 5 mol / L, 6 mol / L, 7 mol / L, 8 mol / L, or a range consisting of any two of these values.
[0192] In some embodiments, the molar concentration of the mixed salt is any value of 1 mol / L, 1.5 mol / L, 2 mol / L, or a range consisting of any two values thereof.
[0193] By controlling the hard template, precipitant, complexing agent, and mixed salt solution within an appropriate range, the coprecipitation reaction is smoother and more efficient. During the coprecipitation reaction, nickel cobalt hydroxide can be precipitated more slowly, stably, and densely on the surface of the hard template, forming a more uniform shell structure on the surface of the hard template, so that the hollow structure has a suitable inner diameter, outer wall thickness, and Dv50, and the positive electrode active material has excellent structural properties, thereby improving the cycle performance and rate performance of the battery.
[0194] In some embodiments, the calcination temperature in step (2) is 700-900°C;
[0195] The calcination time in step (2) is 6-18h.
[0196] In some embodiments, the calcination temperature in step (2) is any value among 700° C., 800° C., 900° C., or a range consisting of any two values thereof.
[0197] In some embodiments, the calcination time in step (2) is any value among 6h, 7h, 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h, 16h, 17h, 18h, or a range consisting of any two values thereof.
[0198] The calcination temperature and time are controlled within an appropriate range to ensure that the hard template can be completely removed to form a hollow structure. At the same time, the stability of the positive electrode active material structure must be ensured. The positive electrode active material has a stable hollow structure to improve the cycle performance and rate performance of the battery.
[0199] [Positive electrode]
[0200] The positive electrode sheet includes a positive electrode current collector and a positive electrode film layer formed on at least a portion of the surface of the positive electrode current collector. The positive electrode film layer includes a positive electrode active material in some embodiments.
[0201] In some embodiments, the surface density of the positive electrode film layer is 24 to 46 mg / cm 2 .
[0202] The coating density of the positive electrode film layer is obtained by measuring the coating weight (g) of the positive electrode film layer on one side and the coating area (cm 2 Specifically, the coating area density of the positive electrode film layer = the coating weight of the positive electrode film layer on one side (g) / the coating area of the positive electrode film layer (cm 2 ).
[0203] The positive electrode film layer may further include a conductive agent to improve the conductivity of the positive electrode. The conductive agent may be selected from one or more of Super P, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphite, graphene, and carbon nanofibers.
[0204] The positive electrode film layer may further include a binder to firmly bond the positive electrode active material and optional conductive agent to the positive electrode current collector. The binder may be at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyacrylic acid (PAA), polyvinyl alcohol (PVA), ethylene vinyl acetate copolymer (EVA), styrene-butadiene rubber (SBR), carboxymethyl cellulose (CMC), sodium alginate (SA), polymethacrylic acid (PMA), and carboxymethyl chitosan (CMCS).
[0205] The positive electrode current collector can be a conductive carbon sheet, metal foil, carbon-coated metal foil, porous metal plate, or a composite current collector. The conductive carbon material of the conductive carbon sheet can be selected from one or more of Super P, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphite, graphene, and carbon nanofibers. The metal material of the metal foil, carbon-coated metal foil, and porous metal plate can each be independently selected from at least one of copper, aluminum, nickel, and stainless steel. The composite current collector can be a composite of metal foil and a polymer-based film.
[0206] In some embodiments, the positive electrode sheet can be prepared by the following method: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components, are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode current collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.
[0207] [Negative electrode]
[0208] The negative electrode sheet includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector. The negative electrode film layer includes a negative electrode active material.
[0209] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on either or both of the two opposite surfaces of the negative electrode current collector.
[0210] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, copper foil may be used as the metal foil. The composite current collector may include a polymer base layer and a metal layer formed on at least one surface of the polymer base material. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy, etc.) on a polymer base material (such as a base material of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0211] In some embodiments, the negative electrode active material may be a negative electrode material for a battery that is well known in the art. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxides, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxides, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode materials for batteries may also be used. These negative electrode materials may be used alone or in combination of two or more.
[0212] In some embodiments, the negative electrode active material has a gram capacity of 600 mAh / g to 2500 mAh / g.
[0213] In some embodiments, the negative electrode active material includes silicon monoxide.
[0214] In some embodiments, based on the total mass of the negative electrode active material, the mass content of silicon monoxide is 20%-100%, optionally 50%-100%.
[0215] In some embodiments, the negative electrode film layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).
[0216] In some embodiments, the negative electrode film layer may further include a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0217] In some embodiments, the negative electrode film layer may optionally further include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).
[0218] In some embodiments, the negative electrode sheet can be prepared by the following method: the components for preparing the negative electrode film layer, such as the negative electrode material, the conductive agent, the binder and any other components, are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.
[0219] [Electrolytes]
[0220] The electrolyte conducts ions between the positive and negative electrodes. This application does not specify the type of electrolyte, and the electrolyte can be selected based on the needs. For example, the electrolyte can be liquid, gel, or solid.
[0221] In some embodiments, the electrolyte is an electrolyte solution comprising an electrolyte salt and a solvent.
[0222] In some embodiments, the electrolyte salt may be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.
[0223] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methylpropyl carbonate, ethylpropyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.
[0224] In some embodiments, the electrolyte may further include additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, and additives that improve battery high or low temperature performance.
[0225] [Isolation film]
[0226] In some embodiments, the secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical and mechanical stability can be selected.
[0227] In some embodiments, the material of the separator can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator can be a single-layer film or a multi-layer composite film, without particular limitation. When the separator is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.
[0228] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator can be formed into an electrode assembly through a winding process or a lamination process.
[0229] In some embodiments, the secondary battery may include an outer packaging that can be used to encapsulate the electrode assembly and the electrolyte.
[0230] In some embodiments, the outer packaging of the secondary battery can be a hard shell, such as a hard plastic shell, an aluminum shell, or a steel shell. Alternatively, the outer packaging of the secondary battery can be a soft shell, such as a pouch-type soft shell. The soft shell can be made of plastic, such as polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0231] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square, or any other shape. For example, FIG2 shows a secondary battery 5 having a square structure as an example.
[0232] In some embodiments, the energy density of the secondary battery is 380-500 Wh / Kg.
[0233] In some embodiments, referring to Figure 3, the outer packaging may include a shell 51 and a cover plate 53. The shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can be formed into an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. The number of electrode assemblies 52 contained in the secondary battery 5 can be one or more, and those skilled in the art can select according to specific actual needs.
[0234] In some embodiments, secondary batteries can be assembled into a battery module. The number of secondary batteries contained in the battery module can be one or more. The specific number can be selected by those skilled in the art according to the application and capacity of the battery module.
[0235] Figure 4 shows an example battery module 4. Referring to Figure 4 , within the battery module 4, multiple secondary batteries 5 may be arranged sequentially along the length of the battery module 4. Of course, any other arrangement is also possible. Furthermore, the multiple secondary batteries 5 may be secured together using fasteners.
[0236] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of secondary batteries 5 are received in the receiving space.
[0237] In some embodiments, the battery modules described above may also be assembled into a battery pack. The battery pack may contain one or more battery modules, and the specific number may be selected by those skilled in the art based on the application and capacity of the battery pack.
[0238] Figures 5 and 6 illustrate an example battery pack 1. Referring to Figures 5 and 6 , the battery pack 1 may include a battery box and multiple battery modules 4 disposed within the battery box. The battery box comprises an upper case 2 and a lower case 3. The upper case 2 can be positioned over the lower case 3 to form an enclosed space for accommodating the battery modules 4. The multiple battery modules 4 can be arranged in any manner within the battery box.
[0239] In addition, the present application also provides an electric device, which includes at least one of the secondary battery, battery module, or battery pack provided in the present application. The secondary battery, battery module, or battery pack can be used as a power source for the electric device, and can also be used as an energy storage unit for the electric device. The electric device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but is not limited thereto.
[0240] As the electrical device, a secondary battery, a battery module or a battery pack can be selected according to its usage requirements.
[0241] Figure 7 shows an example of an electric device. This device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. To meet the high power and high energy density requirements of the secondary battery, a battery pack or battery module can be used.
[0242] Another example device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is generally required to be lightweight and thin, and may use a secondary battery as a power source.
[0243] Example
[0244] Below, the embodiment of the present application is described. The embodiment described below is exemplary and is only used to explain the present application, and is not to be construed as limiting the present application. Where specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. Reagents or instruments used that do not specify the manufacturer are conventional products that can be obtained commercially.
[0245] 1. Preparation method
[0246] Example 1
[0247] 1) Preparation of positive electrode active materials
[0248] Prepare a nickel-cobalt-manganese solution with a molar ratio of nickel, cobalt, and manganese of 97:2:1, adjusting the concentration to 2 mol / L. The soluble raw materials for nickel, cobalt, and manganese are nickel sulfate, cobalt sulfate, and manganese sulfate, respectively. Prepare a 2 mol / L sodium hydroxide solution and a 6 mol / L ammonia solution. Prepare a carbon sphere dispersion with a mass concentration of 10 g / L, place it in a reactor, and stir at 800 rpm for 120 minutes until uniformly dispersed. Carbon sphere specifications: 0.25 μm diameter.
[0249] The nickel-cobalt-manganese solution, sodium hydroxide solution, and ammonia solution were simultaneously added to a reactor for a coprecipitation reaction at 800 rpm, 60°C, and 6 hours. The flow rates of the three solutions were adjusted to 0.5 L / min for the sodium hydroxide solution, 0.7 L / min for the ammonia solution, and 0.2 L / min for the nickel-cobalt-manganese solution. The pH of the system was controlled at 10.8. The ratio of the weight of the carbon spheres to the total weight of the nickel, cobalt, and manganese in the nickel-cobalt-manganese solution was 1:19.
[0250] After the coprecipitation reaction is completed, the reaction material overflows into the aging kettle, some washing additives are added, and stirred for 1 hour. The material is then dehydrated, washed, dehydrated twice, dried, screened, and demagnetized to obtain a positive electrode active material precursor with a carbon ball as the center.
[0251] The positive electrode active material precursor and lithium carbonate are uniformly mixed in a certain proportion, wherein the Li / Me molar ratio is 1.02; Me is the total molar content of nickel, cobalt and manganese.
[0252] The mixed materials are placed in an oxygen atmosphere furnace, the heating rate is set to 5°C / min, and the temperature is kept at 705°C for 6 hours. The atmosphere is required to have an oxygen content of ≥98%, and then cooled with the furnace.
[0253] The material obtained after calcination was subjected to roller crushing, ultracentrifugal grinding and pulverization, and then sieved through a 400-mesh sieve to obtain the positive electrode active material.
[0254] 2) Preparation of positive electrode sheet
[0255] The above-mentioned positive electrode active material, conductive agent carbon black, and binder polyvinylidene fluoride (PVDF) are added to N-methylpyrrolidone in a mass ratio of 97:1:2, and mixed and stirred for 3 hours to obtain a positive electrode slurry; then it is evenly coated on the positive electrode current collector aluminum foil, and after drying, cold pressing, and slitting, a positive electrode sheet is obtained.
[0256] 3) Preparation of negative electrode sheet
[0257] Artificial graphite doped with silicon oxide, conductive agent carbon black, carbon nanotubes (CNT), binder styrene-butadiene rubber (SBR), and thickener sodium hydroxymethyl cellulose (CMC) are added into deionized water in a weight ratio of 94.5:1:0.375:2.8:1.325, wherein the mass fraction of silicon oxide is 70%, based on the mass of artificial graphite and silicon oxide, and mixed and stirred for 0.5-6 hours to obtain a negative electrode slurry; the negative electrode slurry is evenly coated on the negative electrode current collector copper foil in layers, and dried, cold pressed, and cut to obtain a negative electrode sheet.
[0258] 4) Electrolyte
[0259] In an argon atmosphere glove box (H2O <0.1ppm, O2 <0.1ppm), the lithium salt LiPF6 / LIFSI was dissolved in an organic solvent of ethylene carbonate / ethyl methyl carbonate / diethyl carbonate / fluoroethylene carbonate (volume ratio of 1:1:1:1) and stirred evenly to obtain an electrolyte with a lithium salt concentration of 1 mol / L.
[0260] 5) Isolation film
[0261] A polypropylene film is used as a base film, and 1 micron aluminum oxide and 1 micron polyvinylidene fluoride are coated on the base film.
[0262] 6) Preparation of batteries
[0263] The positive electrode sheet, separator, and negative electrode sheet are stacked in order, with the separator positioned between the positive and negative electrode sheets to provide isolation. The cells are then wound to obtain a bare cell. The tabs are welded to the bare cell and placed in an aluminum shell. The cells are then baked at 80°C to remove moisture. The electrolyte is then injected and sealed to obtain an uncharged battery. The uncharged battery then undergoes a series of steps, including resting, hot and cold pressing, formation, shaping, and capacity testing, to obtain the lithium battery product of Example 1.
[0264] Examples 2 to 24
[0265] The preparation methods of the batteries of Examples 2 to 24 are similar to those of the battery of Example 1, but the components of the positive electrode active materials and the preparation methods thereof are adjusted. The specific parameters are shown in Table 1.
[0266] Comparative Example 1
[0267] The preparation method of the battery of Comparative Example 1 is similar to that of the battery of Example 1, but no hard template of carbon spheres is added during the coprecipitation reaction. The preparation method is as follows:
[0268] Comparative Examples 2-3
[0269] The batteries of Comparative Examples 2 to 3 were prepared in a similar manner to the battery of Example 1, but the parameters of the preparation method of the positive electrode active material were adjusted. The specific parameters are shown in Table 1.
[0270] Comparative Example 4
[0271] The battery preparation method of Comparative Example 4 is similar to that of Example 21, but the hard template of carbon spheres is not added during the reaction process. The specific parameters are shown in Table 1.
[0272] Comparative Examples 5-6
[0273] The battery preparation methods of Comparative Examples 5 to 6 are similar to those of Example 21, but the parameters of the preparation method of the positive electrode active material are adjusted. The specific parameters are shown in Table 1.
[0274] 2. Performance Testing
[0275] 1. Performance test of positive electrode active materials
[0276] 1) Inner diameter test of hollow structure
[0277] A conductive adhesive was applied to the sample table, and the powdered samples of the positive electrode active materials in each embodiment and comparative example were spread on the conductive adhesive. The unadhered powder was blown away with an ear bulb, and gold was sprayed. The particles of the powdered sample were cross-sectioned using argon plasma. A scanning electron microscope (e.g., ZEISS Sigma 300) was used at an accelerating voltage of 10 kV and an emission current of 10 mA to obtain a scanning electron microscope photograph of the powdered sample. The inner diameter of the hollow structure was measured based on the SEM image. At least three samples were measured, and at least 50 data points were measured for each sample. The number average was taken as the inner diameter of the hollow structure of the sample.
[0278] 2) Porosity test
[0279] The porosity of the positive electrode active material can be measured using any method known in the art. For example, the porosity is measured using the gas displacement method according to GB / T 24586. Porosity = (V1 - V2) / V1 * 100%, where V1 is the apparent volume of the sample and V2 is the actual volume of the sample.
[0280] 3) The outer wall thickness of the hollow structure
[0281] A conductive adhesive was applied to the sample table, and the powdered samples of the positive electrode active materials in each embodiment and comparative example were spread on the conductive adhesive. The unadhered powder was blown away with an ear bulb, and gold was sprayed. The particles of the powdered sample were cross-sectioned using argon plasma. A scanning electron microscope (e.g., ZEISS Sigma 300) was used with an accelerating voltage of 10 kV and an emission current of 10 mA to obtain a scanning electron microscope photograph of the powdered sample. The outer wall thickness of the hollow structure was measured according to the SEM image. At least three samples were measured, and at least 50 data were measured for each sample. The number average was taken as the outer wall thickness of the hollow structure of the sample.
[0282] 4) Specific surface area test
[0283] Refer to GB / T 19587-2017, "Determination of Specific Surface Area of Solid Substances by Gas Adsorption BET Method." The TriStar II 3020 instrument was used for the measurement. The cathode active material was dispersed in a dispersant (ethanol) and ultrasonicated for 30 minutes. The resulting material was then dried in a vacuum drying oven and measured using a specific surface area meter.
[0284] 4) Dv50 test
[0285] According to the particle size distribution laser diffraction method specified in GB / T 19077-2016, 0.1g to 0.13g of the positive electrode active material sample to be tested was weighed into a 50mL beaker, 5g of anhydrous ethanol was added, a stirring bar approximately 2.5mm in diameter was placed, and the sample was sealed with plastic wrap. After ultrasonic treatment for 5 minutes, the sample was transferred to a magnetic stirrer and stirred at 500 rpm for at least 20 minutes. Two samples were collected from each batch for testing. Testing was performed using a Mastersizer 2000E laser particle size analyzer from Malvern Instruments Ltd., UK. Dv50 is the particle size corresponding to the cumulative volume distribution percentage of the secondary particles of the positive electrode active material reaching 50%.
[0286] 5) SPAN test
[0287] According to the particle size distribution laser diffraction method specified in GB / T 19077-2016, 0.1g to 0.13g of the positive electrode active material sample to be tested was weighed into a 50mL beaker. 5g of anhydrous ethanol was added, and a stirring bar (approximately 2.5mm in diameter) was placed in the beaker, which was then sealed with plastic wrap. The sample was ultrasonically treated for 5 minutes, then transferred to a magnetic stirrer and stirred at 500 rpm for at least 20 minutes. Two samples were taken from each batch for testing. Testing was performed using a Mastersizer 2000E laser particle size analyzer from Malvern Instruments Ltd., UK. Where SPAN = (Dv90 - Dv10) / Dv50, where Dv90 of the secondary particles is the particle size at which the cumulative volume distribution percentage of the positive electrode active material reaches 90%, Dv50 of the secondary particles is the particle size at which the cumulative volume distribution percentage of the positive electrode active material reaches 50%, and Dv10 of the secondary particles is the particle size at which the cumulative volume distribution percentage of the positive electrode active material reaches 10%.
[0288] 6)(101) crystal surface area
[0289] The (101) crystal surface area was measured by X-ray powder diffractometer (XRD, instrument model: Bruker D8ADVANCE), with Cu Kα as the target; the voltage and current were 40 kV / 40 mA, the scanning angle range was 5° to 80°, the scanning step was 0.00836°, and the time per step was 0.3 s.
[0290] 7) Testing method for primary particle size
[0291] After imaging with a 500x scanning electron microscope (ZEISS Sigma-02-33, Germany), 200 to 600 primary particles of the positive electrode active material with complete shapes and no obstructions were randomly selected from the electron microscopic image, and the average value of the longest diameter of the primary particles in the microscopic image was recorded as the average particle size.
[0292] 2. Battery performance test
[0293] 1) Discharge capacity test
[0294] Allow the battery cell to rest at 25°C for 2 hours, ensuring the cell temperature is 25°C. At 25°C, charge the battery cell at 0.1C to a charge cutoff voltage of 4.3V. Continue constant voltage charging at this charge cutoff voltage until the current reaches 0.02C, at which point charging is terminated (where C represents the rated capacity of the battery cell). Allow the battery cell to rest at 25°C for 0.5 hours. At 25°C, discharge the battery cell at 0.1C to a discharge cutoff voltage of 2.5V. Record the total discharge capacity (C0) of the battery cell.
[0295] 2) Energy density test
[0296] Battery cell capacity test: Allow the battery cell to rest at 25°C for 2 hours, ensuring the cell temperature is 25°C. At 25°C, charge the battery cell at 0.1C to the charge cutoff voltage. Continue constant voltage charging at the same charge cutoff voltage until the current reaches 0.05C, at which point the charge is cutoff (where C represents the rated capacity of the battery cell). Allow the battery cell to rest at 25°C for 1 hour. At 25°C, discharge the battery cell at 0.1C to the discharge cutoff voltage. Record the total discharge capacity (C0) and the total discharge energy (E0).
[0297] Battery cell weight measurement: Place the battery cell on an electronic balance until the weight stabilizes, and read the battery cell weight value M0.
[0298] Energy density calculation: Battery cell discharge energy E0 / battery cell weight M0 is the energy density of the battery cell.
[0299] 3) 10~80% SOC charging time test
[0300] Voltage calibration: Place a laminated three-electrode battery cell of the same battery design at 25°C for 30 minutes; at 25°C, charge the battery cell at 0.33C to the charge cut-off voltage, and then continue constant voltage charging at the charge cut-off voltage until the current reaches 0.05C, at which point the charge is cut off (where C represents the rated capacity of the battery cell); place the cell at 25°C for 1 hour; at 25°C, discharge the cell at 0.33C to the discharge cut-off voltage, and record the total discharge capacity C1 of the cell; place the cell at 25°C for 1 hour.
[0301] Charging test: The stacked three-electrode cell was incubated at 25°C for 30 minutes; the discharge voltage was set to 0.33C1DC; the cell was incubated for 5 minutes; the charge capacity was set to xC1CC (the three electrodes monitor the anode potential, and the next step is skipped when the anode potential is 0V). This step was repeated nine times, with x being 5, 4, 4.5, 3, 2, 1, 0.8, 0.5, and 0.33, respectively. The x value corresponding to 0V anode potential and the charge capacity Cx were used.
[0302] 4) Battery cycle capacity retention test
[0303] The secondary batteries prepared in each example and comparative example were charged at a constant current rate of 0.5C to a charge cutoff voltage of 4.25V, then charged at a constant voltage rate to a current of ≤0.05C, allowed to rest for 5 minutes, and then discharged at a constant current rate of 0.33C to a discharge cutoff voltage of 2V, allowed to rest for 5 minutes. This constituted one charge-discharge cycle. The batteries were subjected to cyclic charge-discharge testing using this method until the battery capacity decayed to 80%. The number of cycles at this point is the battery's cycle life at 25°C.
[0304] 3. Analysis of test results of various embodiments and comparative examples
[0305] Batteries of various embodiments and comparative examples were prepared according to the above methods, and various performance parameters were measured. The results are shown in Tables 1, 2, and 3 below.
[0306] Table 1
[0307] Table 2
[0308] Table 3
[0309] According to the above results, the chemical formula of the positive electrode active material in Examples 1 to 24 is LiNi 0.97 Co 0.02 Mn 0.01 O2、LiNi 0.97 Co 0.03 O2、LiNi 0.995 Co 0.004 Mn 0.001 O2、LiNi 0.95 Co 0.04 Mn 0.01 O2、LiNi 0.97 Co 0.02 Sb 0.01 Any one of O2.
[0310] The morphology of the positive electrode active material in Example 4 was measured using a scanning electron microscope (SEM). The test results are shown in Figure 1, which shows that the positive electrode active material has a hollow structure. The positive electrode active materials in Examples 1 to 24 all have a hollow structure, and the inner diameter d1 of the hollow structure is 0.3 μm to 5 μm.
[0311] From the comparison of Examples 1 to 20 with Comparative Example 1, and Example 21 with Comparative Example 4, it can be seen that the positive electrode active material has a hollow structure, which can increase the discharge capacity and energy density of the battery, shorten the charging time of the battery, improve the rate performance of the battery, and improve the cycle performance of the battery.
[0312] From the comparison of Examples 1 to 20 and Comparative Examples 2 to 3, and Example 21 and Comparative Examples 5 to 6, it can be seen that the inner diameter d1 of the hollow structure is 0.3 μm-5 μm, which can improve the cycle performance of the battery. At the same time, the battery has high discharge capacity and energy density, excellent rate performance, and comprehensively improves the electrochemical performance of the battery.
[0313] From the comparison between Examples 2 to 4, 6 to 20 and Examples 1 and 5, it can be seen that the inner diameter d1 of the hollow structure is 1.5 μm-5 μm, which can further improve the cycle performance and rate performance of the battery.
[0314] From the comparison of Examples 4, 7, 11 to 16 with Examples 9 to 10, it can be seen that by controlling the Dv50 of the positive electrode active material and the inner diameter d1 and outer wall thickness d2 of the hollow structure to satisfy: 1≤Dv50 / (d1+d2)≤4, the energy density of the battery can be increased and the rate performance of the battery can be improved.
[0315] As can be seen from Examples 1-24, the outer wall thickness d2 of the hollow structure is 3 μm-10 μm, and the battery has high discharge capacity and energy density, excellent rate performance and cycle performance, and comprehensively improves the electrochemical performance of the battery. A comparison of Examples 2-4 and 6-20 with Examples 1 and 5 shows that the outer wall thickness d2 of the hollow structure is 3 μm-7 μm, which can further improve the cycle performance and rate performance of the battery.
[0316] Comparing Examples 4, 7, and 10 to 16 with Example 9 shows that the Dv50 of the positive electrode active material is 5 μm to 15 μm, which can improve the energy density and rate performance of the battery. Comparing Examples 4, 7, and 11 to 16 with Examples 9 to 10 shows that the Dv50 of the positive electrode active material is 8 μm to 10 μm, which can further improve the energy density and rate performance of the battery.
[0317] As can be seen from Examples 1-24, the porosity of the positive electrode active material is 0-20%, and the batteries have high discharge capacity and energy density, excellent rate performance and cycle performance, and comprehensively improve the battery's electrochemical performance. A comparison of Examples 2-4, 6-8, and 13-16 with Examples 1 and 5 shows that the porosity of the positive electrode active material is 2%-15%, which can increase the battery's discharge capacity and energy density, and improve the battery's rate performance and cycle performance.
[0318] It can be seen from Examples 1 to 24 that the specific surface area of the positive electrode active material is 0.4 m 2 / g-1.4m 2 / g, the battery has high discharge capacity and energy density, excellent rate performance and cycle performance, and comprehensively improves the electrochemical performance of the battery
[0319] Comparing Examples 4, 15-16 with Examples 13-14, it can be seen that the SPAN of the positive electrode active material is 1-1.5, which can improve the discharge capacity of the battery. Comparing Examples 4, 15 with Examples 13-14, 16, it can be seen that the SPAN of the positive electrode active material is 1.2-1.4, which can take into account both the cycle performance and rate performance of the battery, and comprehensively improve the electrochemical performance of the battery.
[0320] It can be seen from Examples 1 to 24 that the (010) crystal plane area of the positive electrode active material is greater than or equal to 6 μm 2 The battery has high discharge capacity and energy density, excellent rate performance and cycle performance, and comprehensively improves the electrochemical performance of the battery.
[0321] Comparing Examples 17 to 19 with Example 20 shows that the primary particle size of the positive electrode active material is 0.1-0.8 μm, which can increase the discharge capacity and energy density of the battery and improve the battery's rate performance. Comparing Examples 18 to 19 with Examples 17 and 20 shows that the primary particle size of the positive electrode active material is 0.15-0.3 μm, which can improve the battery's cycle performance.
Claims
1. A positive electrode active material, It is characterized in that The chemical formula of the positive electrode active material is Li a Ni x Co y M 1-x-y O 2 , Wherein, M includes one or more of Mn, Al, B, Zr, Sr, Y, Sb, W, Ti, Mg, and Nb, 0.55≤x≤1.0, 0≤y≤0.45, and 0.8≤a≤1.2, and the positive electrode active material is a hollow structure, and the inner diameter d1 of the hollow structure is 0.3μm-5μm.
2. The positive electrode active material according to claim 1, It is characterized in that The chemical formula Li a Ni x Co y M 1-x-y O 2 , 0.9≤x≤1.0, 0≤y≤0.1, 0.8≤a≤1.2, optionally 0.95≤x≤0.995, 0≤y≤0.05, 0.8≤a≤1.
2.
3. The positive electrode active material according to claim 1 or 2, It is characterized in that The inner diameter d1 of the hollow structure is 1.5 μm-5 μm.
4. The positive electrode active material according to any one of claims 1 to 3, It is characterized in that The positive electrode active material satisfies the following relationship: 1≤Dv50 / (d1+d2)≤4, Wherein d1 μm is the inner diameter of the hollow structure, d2 μm is the outer wall thickness of the hollow structure, and Dv50 μm is the Dv50 of the positive electrode active material.
5. The positive electrode active material according to any one of claims 1 to 4, It is characterized in that The thickness d2 of the outer wall of the hollow structure is 3 μm-10 μm, and can be optionally 3 μm-7 μm.
6. The positive electrode active material according to any one of claims 1 to 5, It is characterized in that The Dv50 of the positive electrode active material is 5 μm-15 μm, and can be 8 μm-10 μm.
7. The positive electrode active material according to any one of claims 1 to 6, It is characterized in that The porosity of the positive electrode active material is 0-20%, and can be optionally 2%-15%.
8. The positive electrode active material according to any one of claims 1 to 7, It is characterized in that The specific surface area of the positive electrode active material is 0.4 m 2 / g-1.4m 2 / g.
9. The positive electrode active material according to any one of claims 1 to 8, It is characterized in that The SPAN of the positive electrode active material is 1-1.5, and can be 1.2-1.
4.
10. The positive electrode active material according to any one of claims 1 to 9, It is characterized in that The (010) crystal plane area of the positive electrode active material is greater than or equal to 6 μm 2 .
11. The positive electrode active material according to any one of claims 1 to 10, It is characterized in that The primary particle size of the positive electrode active material is 0.1-0.8 μm, and can be 0.15-0.3 μm.
12. A method for preparing a positive electrode active material, It is characterized in that The method comprises steps (1) and (2): Step (1): Mix a mixed source containing a nickel source and a cobalt source with a hard template, a complexing agent, and a precipitant to perform a coprecipitation reaction to obtain a precursor. Optionally, the mixed source contains an M source. Step (2): calcining the precursor and the lithium source to obtain the positive electrode active material, The chemical formula of the positive electrode active material is Li a Ni x Co y M 1-x-y O 2 , Among them, M includes one or more of Mn, Al, B, Zr, Sr, Y, Sb, W, Ti, Mg, and Nb, 0.55≤x≤1.0, 0≤y≤0.45, and 0.8≤a≤1.
2. The positive electrode active material has a hollow structure, and the inner diameter of the hollow structure is 0.3μm to 5μm.
13. The preparation method according to claim 12, It is characterized in that The chemical formula Li a Ni x Co y M 1-x-y O 2 , 0.9≤x≤1.0, 0≤y≤0.1, 0.8≤a≤1.2, optionally 0.95≤x≤0.995, 0≤y≤0.05, 0.8≤a≤1.
2.
14. The preparation method according to claim 12 or 13, It is characterized in that The average diameter of the hard template is 0.2 μm-3 μm, and can be 1 μm-3 μm.
15. The preparation method according to any one of claims 12 to 14, It is characterized in that The hard template includes one or more of carbon-nitrogen composite balls, carbon balls, phenolic resin microballs, and melamine resin microballs, and optionally includes phenolic resin balls.
16. The preparation method according to any one of claims 12 to 15, It is characterized in that The ratio of the weight of the hard template added in step (1) to the total weight of the nickel element and the cobalt element in the mixed source is 1:20-3:4, Alternatively, the ratio of the weight of the hard template added in the step (1) to the total weight of the nickel element, the cobalt element and the M element in the mixed source is 1:20-3:
4.
17. The preparation method according to any one of claims 12 to 16, It is characterized in that The pH value of the coprecipitation reaction in step (1) is 9-13.
18. The preparation method according to any one of claims 12 to 17, It is characterized in that The reaction temperature of the co-precipitation reaction in step (1) is 60-85°C.
19. The preparation method according to any one of claims 12 to 18, It is characterized in that The reaction time of the co-precipitation reaction in step (1) is 5-20 hours.
20. The preparation method according to any one of claims 12 to 19, It is characterized in that The stirring speed of the co-precipitation reaction in step (1) is 200-900 rpm.
21. The preparation method according to any one of claims 12 to 20, It is characterized in that The step (1) specifically comprises: Prepare a hard template solution with a mass concentration of 1-10g / L, a precipitant solution with a molar concentration of 1-2mol / L, a complexing agent solution with a molar concentration of 4-8mol / L, A mixed salt solution having a total molar concentration of nickel and cobalt of 1-2 mol / L, wherein the mixed salt solution may further contain M element; The precipitant solution, the complexing agent solution and the mixed salt solution are combined and added into the hard template solution; The coprecipitation reaction is carried out to obtain the precursor.
22. The preparation method according to any one of claims 12 to 21, It is characterized in that The calcination temperature in step (2) is 700-900°C; The calcination time in the step (2) is 6-18 hours.
23. A positive electrode sheet, It is characterized in that The positive electrode sheet comprises the positive electrode active material according to any one of claims 1 to 10 or the positive electrode active material prepared by the preparation method according to any one of claims 12 to 22.
24. A secondary battery, It is characterized in that Including the positive electrode sheet as described in claim 23.
25. An electrical device, It is characterized in that Includes the secondary battery as claimed in claim 24.
Citation Information
Patent Citations
Preparation method of nickel-cobalt-manganese / aluminum layered cathode material with large (010) crystal face
CN112086616A
Hollow porous ternary positive electrode material, preparation method thereof and lithium ion battery
CN113830844A
Process for preparing uniform hollow-shaped cathode material for lithium secondary battery
KR1020130000138A
KR20190038490A